The Use of Narrative, Dialogue and Critical Reflection in the Development of Women as School Leaders - Joanne E. Cooper (Educational Considerations, 1995)
Through the recursive process of working alone and collectively, the combination of narrative, dialogue and critical reflection offers possibilities for more feminist, collaborative processes in schools and creates relationships in which conversations can take place.